The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fpsyt.2017.00191
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Neuroplasticity to Augment Cognitive Remediation in Schizophrenia

Abstract: There is a burgeoning need for innovative treatment strategies to improve the cognitive deficits in schizophrenia. Cognitive remediation (CR) is effective at the group level, but the variability in treatment response is large. Given that CR may depend on intact neuroplasticity to produce cognitive gains, it is reasonable to combine it with strategies that harness patients’ neuroplastic potential. In this review, we discuss two non-pharmacological approaches that can enhance neuroplasticity and possibly augment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 89 publications
1
14
0
Order By: Relevance
“…Recent work in SZ patients showed that supported physical exercise training resulted in moderate improvements in several domains of cognition across a 12 week period . Converging evidence suggests that physical activity can enhance neuroplasticity by regulating growth factors such as BDNF, which may augment treatments directly training cognition . Thus, it is possible that the pro‐cognitive effects of exercise therapy can extend to BD, and we anticipate that multimodal interventions targeting modifiable lifestyle risk factors such as exercise, sleep and diet alongside cognitive training, might be one of the most powerful means by which to enhance cognitive functioning in the illness.…”
Section: Future Perspectivesmentioning
confidence: 96%
“…Recent work in SZ patients showed that supported physical exercise training resulted in moderate improvements in several domains of cognition across a 12 week period . Converging evidence suggests that physical activity can enhance neuroplasticity by regulating growth factors such as BDNF, which may augment treatments directly training cognition . Thus, it is possible that the pro‐cognitive effects of exercise therapy can extend to BD, and we anticipate that multimodal interventions targeting modifiable lifestyle risk factors such as exercise, sleep and diet alongside cognitive training, might be one of the most powerful means by which to enhance cognitive functioning in the illness.…”
Section: Future Perspectivesmentioning
confidence: 96%
“…BDNF is associated with synaptogenesis and neurogenesis which may foster improved cognition ( Cotman et al, 2007 ; Lu et al, 2013 ; Brigadski and Leßmann, 2014 ; Borror, 2017 ). Notably, an increased level of BDNF was observed during physical exercises and up to 60 min after cessation of the acute bout of physical exercises ( Knaepen et al, 2010 ; Piepmeier and Etnier, 2015 ; Dinoff et al, 2017 ). Based on this observation, the “facilitation effects” of acute physical exercises seem transient and time-constrained ( Fissler et al, 2013 ).…”
Section: Neurophysiological Mechanisms Of Motor-cognitive Trainingmentioning
confidence: 98%
“…A recent meta‐analysis has shown that physical exercise can improve cognition in schizophrenia compared to non‐aerobic control activities. These encouraging findings have led to a few small pilot studies which found that the combination of cognitive remediation plus aerobic exercise leads to differential improvement for some aspects of cognition and functioning. Similarly, based on findings that transcranial direct current stimulation (tDCS) may improve selected aspects of cognition in schizophrenia, a few small pilot studies have reported differential benefits of brief cognitive remediation plus tDCS (versus sham) interventions on trained cognitive tasks.…”
Section: Interventions For Cognitive Impairmentsmentioning
confidence: 99%
“…Aside from oxytocin, studies have started to examine the possibility of improving social cognition in schizophrenia through physical exercise and neurostimulation with tDCS. Only a few studies have examined the effects of exercise, providing early encouraging results (g=0.71, based on three studies). An initial study by our team found that a single session of tDCS (vs. sham), administered over the prefrontal cortex, significantly improved facial identification task performance, though not other social cognitive domains.…”
Section: Interventions For Cognitive Impairmentsmentioning
confidence: 99%